The growth of weakly coupled graphene sheets from silicon carbide powder - Kiselov, V.S.; Lytvyn, P.M.; Nikolenko, A.S.; Strelchuk, V.V.; Stubrov, Yu.Yu.; Tryus, M.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
A simple method for production of weakly coupled graphene layers by hightemperature sublimation of polycrystalline SiC is presented. The method allows manufacturing carbon-based composite with a high content of weakly coupled graphene layers in large-scale production. The study of the obtained carbon-based material by means of scanning electron microscopy, Raman spectroscopy and atomic force microscopy detected graphene plates with lateral size of up to tens of micrometers. The obtained graphene sheets are shown to have very high crystal perfection, low concentration of defects and weak interlayer coupling, which depends on the growth conditions. The proposed method of producing graphene-based composites is supposed to be very promising due to its relative simplicity and high output.